2021
DOI: 10.1186/s13046-021-02140-0
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SGO1-AS1 inactivates TGFβ signaling by facilitating TGFB1/2 mRNA decay and inhibits gastric carcinoma metastasis

Abstract: Background Although thousands of long noncoding RNAs (lncRNAs) have been annotated, only a few lncRNAs have been characterized functionally. In this study, we aimed to identify novel lncRNAs involved in the progression of gastric carcinoma (GC) and explore their regulatory mechanisms and clinical significance in GC. Methods A lncRNA expression microarray was used to identify differential lncRNA expression profiles between paired GCs and adjacent no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
(56 reference statements)
0
12
0
Order By: Relevance
“… 352 However, depending on the cell type and physiological environment, TGF-β1 can exhibit opposite effects. TGF-β1 has a significant growth inhibitory effect on cells of epithelial origin by preventing cells from the G1-S phase in vitro, 353 , 354 and TGF-β1 expression is often reduced or absent in malignant tumors. 355 TGF-β1 can also inhibit the proliferation and induce apoptosis of GC cell lines HSC-39 and HSC-43 in vitro.…”
Section: Signaling Pathways In Gastric Cancer and Therapeutic Implica...mentioning
confidence: 99%
“… 352 However, depending on the cell type and physiological environment, TGF-β1 can exhibit opposite effects. TGF-β1 has a significant growth inhibitory effect on cells of epithelial origin by preventing cells from the G1-S phase in vitro, 353 , 354 and TGF-β1 expression is often reduced or absent in malignant tumors. 355 TGF-β1 can also inhibit the proliferation and induce apoptosis of GC cell lines HSC-39 and HSC-43 in vitro.…”
Section: Signaling Pathways In Gastric Cancer and Therapeutic Implica...mentioning
confidence: 99%
“…SGOL1-AS1, has been previously studied in other cancer types, with varied associations between healthy and cancerous tissue in colorectal cancer, and gastric carcinoma ( Asad Samani and Peymani, 2021 ; Huang et al., 2021 ). Interestingly in the latter, SGOL1-AS1 has been characterized as a cytoplasmic lncRNA that is downregulated in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly in the latter, SGOL1-AS1 has been characterized as a cytoplasmic lncRNA that is downregulated in gastric cancer cells. The different cellular localization observed in gastric cancer and AML could possibly reflect distinct SGOL1-AS1 isoforms expressed ( Huang et al., 2021 ). This may also explain why in gastric carcinoma SGOL1-AS1 is a marker of good prognosis ( Huang et al., 2021 ), while we observed that in AML patients high SGOL1-AS1 expression is associated with poor survival across different subtypes of AML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transforming growth factor-β (TGF-β) family is a group of structurally related proteins, is involved many cellular functions, including EMT and migration, and many human diseases, including vascular diseases, autoimmune disorders, and carcinogenesis ( Syed, 2016 ). LncRNA Shugoshin-like protein 1-antisense 1 (SGO1-AS1) facilitates TGF-β1/2 mRNA decay by competitively binding to the PTBP1 protein, leading to impaired TGF-β production, and preventing EMT and metastasis ( Huang et al, 2021 ). Extracellular signal-regulated kinase (ERK) cascade can regulates proliferation, differentiation, survival, and apoptosis of cells, the mitogen extracellular signal-regulated kinase (MEK) functions as an upstream essential protein of ERK ( Liu W. et al, 2015 ).…”
Section: Lncrnas Regulate Emt-induced Metastasis By Mediating the Sig...mentioning
confidence: 99%